Arteriovenous Access Type and Risk of Mortality, Hospitalization, and Sepsis Among Elderly Hemodialysis Patients: A Target Trial Emulation Approach - Lyu, Beini; Chan, Micah R; Yevzlin, Alexander S; Gardezi, Ali; Astor, Brad C (American journal of kidney diseases, 2022)
Evidence is mixed regarding the optimal choice of the first permanent vascular access for elderly patients receiving hemodialysis (HD). Lacking data from randomized controlled trials, we used a target trial emulation approach to compare arteriovenous fistula (AVF) versus arteriovenous graft (AVG) creation among elderly patients receiving HD. Retrospective cohort study. Elderly patients included in the US Renal Data System who initiated HD with a catheter and had an AVF or AVG created within 6 months of starting HD. Creation of an AVF versus an AVG as the incident arteriovenous access. All-cause mortality, all-cause and cause-specific hospitalization, and sepsis. Target trial emulation approach, high-dimensional propensity score and inverse probability of treatment weighting, and instrumental variable analysis using the proclivity of the operating physician to create a fistula as the instrumental variable. A total of 19,867 patients were included, with 80.1% receiving an AVF and 19.9% an AVG. In unweighted analysis, AVF creation was associated with significantly lower risks of mortality and hospitalization, especially within 6 months after vascular access creation. In inverse probability of treatment weighting analysis, AVF creation was associated with lower incidences of mortality and hospitalization within 6 months after creation (hazard ratios of 0.82 [95% CI, 0.75-0.91] and 0.82 [95% CI, 0.78-0.87] for mortality and all-cause hospitalization, respectively), but not between 6 months and 3 years after access creation. No association between AVF creation and mortality, sepsis, or all-cause, cardiovascular disease-related, or infection-related hospitalization was found in instrumental variable analyses. However, AVF creation was associated with a lower risk of access-related hospitalization not due to infection. Potential for unmeasured confounding, analyses limited to elderly patients, and absence of data on actual access use during follow-up. Using observational data to emulate a target randomized controlled trial, the type of initial arteriovenous access created was not associated with the risks of mortality, sepsis, or all-cause, cardiovascular disease-related, or infection-related hospitalization among elderly patients who initiated HD with a catheter.